Exploring the electrocatalytic sites of carbon nanotubes for NADH detection: an edge plane pyrolytic graphite electrode study. - Banks, C; Compton, R (2005)
The electrocatalytic properties of multi-walled carbon nanotube modified electrodes toward the oxidation of NADH are critically evaluated. Carbon nanotube modified electrodes are examined and compared with boron-doped diamond and glassy carbon electrodes, and most importantly, edge plane and basal pyrolytic graphite electrodes. It is found that CNT modified electrodes are no more reactive than edge plane pyrolytic graphite electrodes with the comparison with edge plane and basal plane pyrolytic graphite electrodes allowing the electroactive sites for the electrochemical oxidation of NADH to be unambiguously determined as due to edge plane sites. Using these highly reactive edge plane sites, edge plane pyrolytic graphite electrodes are examined with cyclic voltammetry and amperometry for the electroanalytical determination of NADH. It is demonstrated that a detection limit of 5 microM is possible with cyclic voltammetry or 0.3 microM using amperometry suggesting that edge plane pyrolytic graphite electrodes can conveniently replace carbon nanotube modified glassy carbon electrodes for biosensing applications with the relative advantages of reactivity, cost and simplicity of preparation. We advocate the routine use of edge plane and basal plane pyrolytic graphite electrodes in studies utilising carbon nanotubes particularly if 'electrocatalytic' properties are claimed for the latter.